The major environmental disasters produced by the mining - metallurgical activity worldwide: causes and consequences ecological and social - Rodríguez, Roberto (2009)
This study aims to analyze the main causes of major environmental disasters caused by mining-metallurgical activities worldwide. 363 cases were analyzed, including significant incidents and disasters, as reflected in various databases, reports and publications. The main causes of these disasters should be noted: 1) insufficient or improper environmental impact study (EIA), 2) the failure of waste storage structures ( Tailing dams, tailings piles leaching, etc.). 3) No using best available techniques (BAT) in mines and metallurgical activities, 4) errors in the design of facilities, 5) failure to use appropriate security measures according to the risks involved. The magnitude of these disasters has been increasing for several reasons: the negligent behaviour of firms and administrations, the existence of nearby villages, the unique and fragile ecology of the area of location of mining operations, the absence in many cases of emergency plans and facilities, lack of a plan of land and extensive mining activity in a specific area. For this reasons the European Union has forced all productive sectors to develop the BAT document, in order to reduce these disasters and their environmental effects.